Harnessing the Power of Distributed Systems for Scalable Cloud Computing A Review of Advances and Challenges - Taher, Hanan; Zeebaree, Subhi R. M. (AI Society & STMIK Indonesia, 2024)
In the realm of cloud computing, the literature defines scalability as the inherent ability of a system, application, or infrastructure to adapt and accommodate varying workloads or demands efficiently. It encompasses the system's capability to handle increased or decreased usage with compromising performance, responsiveness, or stability. In this paper, a comprehensive review is presented regarding the scalability in the cloud computing network. In addition, the research community define the scalability as a dynamic attribute, emphasizing its ability to facilitate both horizontal and vertical scaling. Horizontal scalability involves adding or removing instances or nodes to distribute workloads across multiple resources, while vertical scalability focuses on enhancing the capacity of existing resources within a single entity. They established a global frameworks to evaluate scalability, often emphasizing response time, throughput, resource utilization, and cost-efficiency as critical metrics. These metrics serve as benchmarks to assess the system's ability to scale effectively without compromising performance or incurring unnecessary costs [1]. The literature underscores scalability's interconnectedness with elasticity, highlighting the need for on-demand resource provisioning and de-provisioning to maintain an agile and adaptable infrastructure. Overall, in academic papers, cloud scalability is portrayed as a fundamental attribute crucial for modern computing infrastructures, enabling systems to flexibly and efficiently adapt to dynamic computing needs.